2013
DOI: 10.1159/000345779
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Heart Rate Variability in Patients with ST-Segment Elevation Acute Myocardial Infarction Treated by Primary Angioplasty

Abstract: Objectives: The aim of our study was to assess the prognostic value of heart rate variability (HRV) in ST-segment elevation acute myocardial infarction (STEMI) patients treated by percutaneous transluminal coronary angioplasty (PTCA) and optimal medical therapy. Methods: We enrolled 182 consecutive patients with a first STEMI (59.1 ± 11 years; 82.4% men) treated by primary PTCA. HRV was assessed on 24-hour Holter ECG recordings before discharge and 1 and 6 months after discharge. The primary end point was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
(38 reference statements)
0
24
1
1
Order By: Relevance
“…HRV was also an independent predictor of increased mortality of patients with myocardial infarction and congestive heart failure (3,4). Autonomic changes have been found to be associated with ischemia in patients with coronary artery disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…HRV was also an independent predictor of increased mortality of patients with myocardial infarction and congestive heart failure (3,4). Autonomic changes have been found to be associated with ischemia in patients with coronary artery disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is however much lower than that reported by Wiliński et al[7] in patients treated by primary PCI (21% in patients < 65 years old and 34% in those ≥ 65 years old), as well as in other smaller dimension studies in which patients had also been treated by primary PCI[9,16]. When considering the subgroup of patients with even more depressed HRV (using the cut-off of SDNN < 50 ms, as in the pivotal study by Kleiger et al[1]), the prevalence of this abnormal parameter was lower in our STEMI patients (5% in our study vs 15% in Kleiger’s study), being somehow similar to that observed also by Erdogan et al[6] (7%) in patients treated by immediate revascularization.…”
Section: Discussionmentioning
confidence: 58%
“…Almost all these studies included both STEMI and NSTEMI patients. More recently, only STEMI patients have been analysed, following treatment by primary PCI: Their long-term mortality rate was reported to be substantially lower than in the pre-primary-PCI era, being possible to calculate it on average around 5% of cases[6,9,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Biochemical markers and other markers such as heart rate variability or white blood cell count are likely to play an increasingly important role in the future of risk stratification for early discharge [23,24,25]. …”
Section: Figmentioning
confidence: 99%